MERS-CoV in a healthcare worker in Jeddah, Saudi Arabia: an index case investigation. Issue 3 (July 2016) - Shalhoub, S.; Abdraboh, S.; Palma, R.; AlSharif, H.; Assiri, N.
Summary: In September 2015, a confirmed case of Middle East respiratory syndrome (MERS) was diagnosed in a healthcare worker in Jeddah, Saudi Arabia. Given the absence of confirmed MERS cases in Jeddah at the time, an epidemiological index case investigation took place. The investigation identified a probable source of an index case who had been in hospital in Jordan in August 2015 while there was an ongoing MERS outbreak and who then subsequently sought medical care in Jeddah.